Centrifugal pump performance subjected to severe off-design operations - Zhu, Jing Song. (2009)
Centrifugal pumps are usually designed to operate near the point of best efficiency but many applications require operation over a wide range of capacity. The occurrence of recirculation and prerotation is accepted to be the determining factor in defining the stability and efficiency of partial flow of pump.